(untitled) (Fiep Bulletin - online, 2014)
The garbage collector and garbage sweeper, is a professional that conserves the plublic park clean by means of collect, sweeping and washing. The absence of works, that boarding the socialeconomic and cultural aspects that carries to the appearing of patologies in this professional population, carry to the making of this work. Compounded by 79 workers of collect and sweepingof garbage, was used a form, so that could inquire the real condition of life of this workers. The obtained results show that the majority (83,54%) are men; and with rent of one or three minimum salary (78,47%); (55,70%) don’t realized trainement; 30,38% at once get injured in the service; being that; 79,16% had retirement of one week cut and perfusion (50%); in lawer limbis, principally at Wednesday (29,17%); although argue the use of EPI (85,76%); 34% related intensive and continue pain in vertebral column during the performance of work. The obtained results suggested that the socialeconomic and cultural lower level, can interfere in fisical mental and social, condition, propritiating favourable conditions to the appearing of several damages to health.